KINETIKA TRANSPOR Co(II) MELALUI TEKNIK MEMBRAN CAIR FASA RUAH SECARA KONSEKUTIF - Riana Dewi; Admin Alif; Hermansyah Aziz (Universitas Andalas, 2009)
ABSTRACT Determination of kinetic analysis of Co(II) ion transport through bulk liquid membranes by consecutive method have been study. The optimum condition was obtained at pH 4 for the intermediate phase and receiving phase at pH near zero, while the source phase at pH 7, oxine concentration in chloroform at source phase is 2.10 M, methyl red concentration in chloroform at receiving phase is 3.10 M. It was found that Co(II) ion receiving phase at optimum condition as 4.40%. Evaluation of Co(II) ion kinetic transport shows k1 as 0.0116 minutes-1 and k4 0.0113 minutes-1. Kinetic transport process of Co(I1) ion through bulk liquid membranes by consecutive method followed first order consecutive irreversible reaction rate low. Consecutive method can used as an alternative method in determination the optimum condition of metals ion transport and kinetic evaluation of mentioned transport metals ion. Keywords : bulk liquid membranes, consecutive, cobalt